Mental Health Wellbeing of School Age Children is Matter: A Study to Evaluate the Effectiveness of a School-Based Mental Health Awareness Program in The Middle Schools in Oman: Mental Health wellbeing of School Age Children - Al Nasiri, Yusra; Al Abri, Aisha; Al Rawahi, Afra; Al Harrasi, Al Anood; Al Shuaibi, Amal; Al Owisi, Amina; Al Rashdi, Arwa; Al Shabibi, Atheer; Al Hakmani, Balaqis; Al Harthi, Shamsa (Journal of Contemporary Medical Sciences, 2022)
Objective: The aim of this study is to assess the effectiveness of a school-based mental health awareness program among school age children. Methods: This was a quantitative study that recruited 178 parents and 150 students from different levels (Grades 5-10) attended the awareness activity at two middle schools in Oman. A convenient sampling approach was utilized. Results: There was a significant different in mood and feelings score between the grades (p=0.001); with grade 10 being the highest disturbed mood changes (M= 23.25, SD= 5.54). The results also showed that 55% of students experienced anxiety. From the analysis, it was found that grade 10 (M=36.15, SD= 18.43, p=0.05) reported higher anxiety than others groups. The results indicated also a strong correlation between experience of bullying and mental health problems (r=0.85). The evaluation of awareness program indicated that 91% of parents reported improvement in knowledge; 89% suggested that many information they were not aware of before. 92% rated the video as informative. 93% agreed that the program activities were entertaining and informative. 92% reported that the activity increased their awareness to observe the changes in their children emotional wellbeing. 98% of parents enjoyed the activities and rated the overall program as effective and very interesting. Conclusion: There is a dire need to conduct various awareness programs in the community. Such programs are not only helpful in improving the community knowledge on the factors influencing children’s mental health, but also assist in identifying the mental health problems at early stage; which may empower them to seek early management for their children. This study suggests an establishment of a mental health program for children in Oman to identify the cases, assess the mental problems affecting children at different ages and refer them for further support and management.